Effectiveness of exercise interventions on physical function in community-dwelling frail older people: an umbrella review protocol. (September 2016) - Jadczak, Agathe D.; Makwana, Naresh; Luscombe-Marsh, Natalie D.; Visvanathan, Renuka; Schultz, Timothy J.
Abstract : Review question/objective: The objectives of this umbrella review are to determine the effectiveness of exercise interventions, alone or in combination with other interventions, for improving physical function in community-dwelling older people who are identified as frail or at risk of frailty, and to identify if any particular intervention type or characteristic is the most effective. Specifically, the review question is: What is the effectiveness of exercise interventions, alone or in combination with other interventions, for improving physical function in community-dwelling older people identified as frail or at risk of frailty?